DIVERSITY OF FISH SPECIES IN THE KEBUN NOPI LAKE, KUANTAN MUDIK SUBDISTRICT, KUANTAN SINGINGI REGENCY, RIAU - Jihan Nabila Sajidah; Deni Efizon; Ridwan Manda Putra (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
Kebun Nopi Lake is a man-made lake that is constructed by damming theKuningRiver. This lake is inhabited by many type of fish species. However, the information on thetype of fish in that area is limited. A study aims to identify and inventory the types of fishcaught in the Kebun Nopi Lake has been conducted on March 2022. Sampling was carriedout 3 times. The fish was captured using nets, small fish scoop , fishing rods and all of fishcaptured were taken and identified. Results shown that there were 5 orders, 9 families, 17genus and 23 species of fishes present in the lake. The largest family was Cyprinidae that wasconsisted of 12 species. the value of species diversity (H') was -1.615 (low), uniformity index(E) -0.52 (low) and species dominance (C) 0.1649 (low). The condition of water quality inshown that temperature was 320C-340C, depth 150 cm–161 cm, brightness 16.5 cm–21 cm,pH 4-6, dissolved oxygen 4.52–5.81 mg/L and free carbon dioxide 15.22–19.97 mg/L.Based on the diversity index, the fish diversity in the Kebun Nopi Lake can be classified aslow.Keywords:man-made lake, Kuning River, Fish Diversity, Water Quality1)Student of the Faculty of Fishheries and Marine Science, Universitas Riau2)Lecturer at the Faculty of Fishheries and Marine Science, Universitas Riau